Linking environmental sustainability and healthcare: The effects of an energy saving intervention in two hospitals - Danae Manika; Diana Gregory-Smith; Victoria K. Wells; Lee Comerford; Lucy Aldrich-Smith (International Journal of Business Science & Applied Management (IJBSAM), 2016)
Set in a real organisational setting, this study examines the challenges of implementing environmentally sustainable behaviour in healthcare. It evaluates the success of a real energy saving behaviour change intervention, based on social marketing principles, which targeted the employees of two National Health Service (NHS) hospitals. It also explores the intervention benefits for three key stakeholders: the organisation/hospitals, hospital employees and patients. A rich secondary dataset containing actual workplace behaviour measures (collected via observations) and self-reported data from employee interviews and patient questionnaires is used for this purpose. The intervention encouraged three employee energy saving actions (called TLC actions): (1) Turn off machines, (2) Lights out when not needed, and (3) Close doors when possible; which led to energy savings and carbon reduction for the two hospitals. Hospital employees reported a greater level of work efficiency as a result of engaging in TLC actions, which increased the 'quiet time' periods in both hospitals. Indirectly, employees' TLC actions also improved patients' quality of sleep (which in turn is positively associated with greater patient hospital experience satisfaction). These findings shed light on the benefits of social marketing interventions targeting energy saving behaviour change for multiple stakeholders in healthcare organisations. They also illustrate connections between environmental sustainability and social and political pillars of corporate social responsibility. Additionally, organisational culture was highlighted as a key challenge in changing practices. To encourage long-term sustainable behaviour, this study recommends a pre-intervention assessment of infrastructure and equipment, the communication of expected benefits to motivate higher involvement of employees, the need for internal green champions and the dissemination of post-intervention feedback on various energy saving and patient indicators.
Keywords: 650; Environmental sustainability; Healthcare organisation; Energy saving intervention; Hospital patient experience; Energy data; Corporate Social Responsibility